2017
DOI: 10.1007/82_2017_1
|View full text |Cite
|
Sign up to set email alerts
|

The Unfolded Protein Response in the Immune Cell Development: Putting the Caretaker in the Driving Seat

Abstract: The endoplasmic reticulum (ER) is the primary site for the folding of proteins destined for the membranous compartment and the extracellular space. This elaborate function is coordinated by the unfolded protein response (UPR), a stress-activated cellular program that governs proteostasis. In multicellular organisms, cells have adopted specialized functions, which required functional adaptations of the ER and its UPR. Recently, it has become clear that in immune cells, the UPR has acquired functions that stretc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 164 publications
0
4
0
Order By: Relevance
“…Importantly, both conventional DCs (cDC) and highly secretory type‐I interferon‐producing pDCs at steady state display a relatively high basal level of XBP1 mRNA splicing . The endonuclease activity of IRE1 contributes to cDC survival during stress exposure in different mucosal tissues, in which they can mount alternatively ATF4‐ or XBP1‐dependent adaptive responses to survive the different specific stressors encountered at their sites of residence . For example, lung‐resident cDCs require IRE‐1 signaling for their survival in the high oxygen tension present in this organ, while cDCs in the intestine do not (Fig.…”
Section: Ire‐1 and Immune Cells Differentiation Or Survivalmentioning
confidence: 99%
“…Importantly, both conventional DCs (cDC) and highly secretory type‐I interferon‐producing pDCs at steady state display a relatively high basal level of XBP1 mRNA splicing . The endonuclease activity of IRE1 contributes to cDC survival during stress exposure in different mucosal tissues, in which they can mount alternatively ATF4‐ or XBP1‐dependent adaptive responses to survive the different specific stressors encountered at their sites of residence . For example, lung‐resident cDCs require IRE‐1 signaling for their survival in the high oxygen tension present in this organ, while cDCs in the intestine do not (Fig.…”
Section: Ire‐1 and Immune Cells Differentiation Or Survivalmentioning
confidence: 99%
“…In most cell types, the IRE1 signaling axis is not active in basal conditions but reporter studies have shown that conventional dendritic cells (cDCs), macrophages and NK cells are exceptions to this rule. 21,22 Compared to splenic T and B cells, NK cells showed basal XBP1 splicing activity, as determined by conventional PCR on sorted splenic immune cell populations (Figure 1A) or by monitoring IRE1 endonuclease activity by means of the ER stress-activated indicator (ERAi) VenusFP reporter mouse line 23 (Figure 1B). Still, compared to type 1 cDCs (cDC1s), the endonuclease activity of IRE1 in NK cells appeared modest, even after stimulation of NK cells with the viral analog poly(I:C) (Figure 1B).…”
Section: Nk Cell Distribution and Function Remain Unaltered Upon Loss...mentioning
confidence: 99%
“…Proteostasis encompasses the dynamic interrelation of processes governing generation and localization of functional proteins ( 1 ). Physiological and pathological factors can impair the balance between protein load and protein processing, resulting into accumulation of improperly folded proteins ( 2 , 3 ). Abnormal protein aggregation is a key feature of several neurodegenerative diseases, including Alzheimer's disease (AD), Parkinson's disease (PD), amyotrophic lateral sclerosis (ALS), Huntington's disease (HD) and prion-related disorders amongst others, collectively classified as protein misfolding diseases (PMDs) ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…XBP1s is constitutively expressed by DCs and high XBP1s is a hallmark of cDC1s across tissues, although the CNS remains to be examined ( 95 , 100 , 101 ). Furthermore, cDC1s activate the IRE1α -XBP1 axis for development, survival in mucosal tissues and cross-presentation of antigens to CD8 + T cells, which may be of relevance in infections with neurotropic viruses ( 2 , 102 ). In addition, cDC1s are highly sensitive to perturbations in XBP1 signaling and counter activate RIDD upon XBP1 loss ( 95 , 101 ).…”
Section: Introductionmentioning
confidence: 99%